The Application of the Concept of Resilience in Aging Research and Older Adult Care: A Focus Group Study - Angevaare, Milou J.; Monnier, A. A.; Joling, K. J.; Smalbrugge, M.; Schellevis, F. G.; Hertogh, C. M. P. M.; Huisman, M. (Frontiers in Medicine, 2020)
Introduction Research incorporating resilience, a concept featuring a positive outcome despite some type of stressor, has the potential to identify possibilities for promotion of the wellbeing of older people. This study aims to gain insight into the value and potential applications of resilience in both research and care practice from the perspective of researchers and care professionals. Specifically, the value of two scientific approaches, the a-priori (i.e. based on a-priori definition of a stressor and outcome) and dynamical systems approaches (i.e. based on mathematically modelled patterns in the real-time response to perturbations), was explored. Methods Focus groups were performed to explore the thoughts of academic researchers from different disciplines in the fields of aging and care, and care professionals on the application of the concept of resilience, including the a-priori and dynamical systems approaches. Analysis of these focus groups was based on the Framework Method. Results Five focus groups were held with a total of nine researchers from different disciplines (e.g. epidemiology, sociology) and 15 older adult care professionals from different professions (e.g. elderly care physician, physiotherapist). The participants described resilience as a concept with value for both aging research and care through its positive connotation and comprehensiveness. Continued research was thought to play an important role in clearing up some of the existing ambiguity surrounding resilience. The importance of resilience in the context of both high and low intensity stressors was underscored. The a-priori and dynamical systems approaches were considered to have their specific advantages and disadvantages on both a conceptual and a feasibility level. Therefore, the use of both approaches, side-by-side and in combination, was suggested. Conclusion This qualitative exploration among researchers and care professionals confirmed that the concept of resilience, including the a-priori and dynamical systems approaches, is valuable. However, more work is necessary before can be delivered on the potential of resilience in aging research and older adult care practice. Greater conceptual and operational clarity can be achieved through: more qualitative studies on the concept, taking the perspective of older people into account and through empirical studies that work with both approaches simultaneously and/or in combination.